MEA6 Deficiency Impairs Cerebellar Development and Motor Performance by Tethering Protein Trafficking - Wang, Xin-Tai; Cai, Xin-Yu; Xu, Fang-Xiao; Zhou, Lin; Zheng, Rui; Ma, Kuang-Yi; Xu, Zhi-Heng; Shen, Ying (Frontiers in Cellular Neuroscience, 2019)
Meningioma expressed antigen 6 (MEA6), also called cutaneous T cell lymphoma-associated antigen 5 (cTAGE5), was initially found in tumor tissues. MEA6 is located in endoplasmic reticulum (ER) exit sites and regulates the transport of collagen, very low density lipoprotein, and insulin. It is also reported that MEA6 might be related to Fahr’s syndrome, which comprises neurological, movement, and neuropsychiatric disorders. Here, we show that MEA6 is critical to cerebellar development and motor performance. Mice with conditional knockout of MEA6 (Nestin-Cre;MEA6F/F) display smaller sizes of body and brain compared to control animals, and survive maximal 28 days after birth. Immunohistochemical and behavioral studies demonstrate that these mutant mice have defects in cerebellar development and motor performance. In contrast, PC deletion of MEA6 (pCP2-Cre;MEA6F/F) causes milder phenotypes in cerebellar morphology and motor behaviors. While pCP2-Cre;MEA6F/F mice have normal lobular formation and gait, they present the extensive self-crossing of PC dendrites and damaged motor learning. Interestingly, the expression of key molecules that participates in cerebellar development, including Slit2 and brain derived neurotrophic factor (BDNF), is significantly increased in ER, suggesting that MEA6 ablation impairs ER function and thus these proteins are arrested in ER. Our study provides insight into the roles of MEA6 in the brain and the pathogenesis of Fahr’s syndrome.